THE SEMANTICS STUDY OF ENGLISH SLANG USED IN THE COLUMN COSMO MAGAZINE - Hidayati Hidayati; Asbah Asbah; Agung A (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2013)
This research entitiled is ”The Semantics Study of English Slang used in the Column Cosmo Magazine” is intended to find out the forms and meaning of slangand also the relative frequency of the use of slang that is used related to their forms and meaning. This research is descriptive qualitative research. To analyze thedata, first of all, the writer describes the data into their forms and meaning by qualitatively. After that, to achieve the objective of research, the researcher is done by quantitatively. The object ofthis research is slang words, phrases, and phrasalverb. The writer analyzes the population of the magazine which are published in 2012, it consists of 6 editions. In collecting the data, the researcher just presents what is found without adding any other information and classifies data based  on the research questions. This study is done by translating based on the dictionary meaning and interpretation of theslang expressions that are found. The result is shown from the total  of the 100 (100%) data observed are the forms of  slang words (51%) can be noun (33,33%), verb (25%), adjective (29,17%), and adverb (12,5%) and also the slang words can be words formation in the form of derivation (7,40%),  compounding (11,11%), Clipping (37,03%), acronym (11,11%), blending (11,11%), proper name (11,11%) and imitation (11,11%),  Phrases(9%) are noun phrase (33,33%), verb phrase (33,33%), and prepositional phrase (33,33%)  and phrasal verb (7%) are in inseparable(0%) and separable (100%). The meaning of slang can be denotative (48,48%), connotative (30,30%), and both of denotative  and connotative meaning (21,21%). In short, it can be said that the most dominant of the meaning of slang in column Cosmo magazine is denotative meaning. Eventhough, the connotative meaning is used to give the deepest meaning and the highest impression of sense of the words and phrases